Philosophy Conference Devoted to the 400th Anniversary of Vilnius University - [autorius nenurodytas], (Problemos, 1978)
In the article by A. Varanavičius, Č. Kalenda, A. Nesavas, T. Sodeika, K. Stoškus, A. Šliogeris, and G. Jatkonis an account on the local philosophy conference held in Vilnius (September 25-26, 1978) is presented. At the Conference papers by philosophers from Lithuania and other Soviet republics including scientists from Moscow, Leningrad, Novosibirsk as well as guests from socialist countries (Poland, the GDR, Czechoslovakia) were presented. The materials deal with the main ideas discussed at the Conference both at the plenary and section meetings.